Some Perspectives on the UN Security Council Reform Proposals - Stojkovski, Ljupcho (Faculty of Law Iustinianus Primus Skopje, 2022)
The calls for reform of the UN Security Council, which are as old as the organization itself, have been in the international spotlight again with the wars in Syria and Ukraine and the vetoes that Russia (and China) used to block any measure regarding them. In this paper, I will briefly present and critically discuss the three groups of proposals that are mostly given for reforming the Council: the enlargement proposals, the proposals for reforms of the working methods of the Council, and the proposals for reforms of the veto. All of these proposals have some merit (albeit different) and try to address some deficiency in the functioning or design of the Council. Therefore, despite the low likelihood of success, all of these reform proposals should be pursued because they (at the very least) serve as a tool for putting pressure on the permanent members to uphold their responsibilities that to the UN and the international community as a whole.
Keywords: UN Security Council; UN Security Council (UNSC); Reform